The Epistemology of Islamic Law and Its Implications for Legal Thought Reform - Samsidar Samsidar (Journal of Nafaqah, 2025)
This article examines the epistemology of Islamic law and its implications for the reform of Islamic legal thought in modern social contexts. The central issue addressed is the epistemological fragmentation within contemporary Islamic legal reform, characterized by the isolated use of bayani reasoning, rational hermeneutics, maqāṣid al-sharī‘ah, and ethical approaches without an integrated evaluative framework. This study employs a normative juridical method using conceptual and doctrinal approaches to analyze the epistemic structure of classical Islamic law and the challenges facing modern reform efforts. The findings indicate that the crisis of Islamic legal reform does not stem from a lack of substantive norms, but from the erosion of epistemological discipline in legal reasoning. The study argues for the reconstruction of an integrative epistemology that reaffirms uṣūl al-fiqh as a structural framework, textual authority as the normative foundation, maqāṣid as an orientation toward justice, and rational reasoning as a controlled contextual instrument. Such reconstruction is essential to preserve legitimacy, methodological coherence, and the adaptive capacity of Islamic law in the contemporary era.